Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Given that [tex]\overrightarrow{OA} = 11x + 6y[/tex], [tex]\overrightarrow{OB} = 4x + 10y[/tex], and [tex]\overrightarrow{CO} = -13x + 11y[/tex], write down each of the following vectors in its simplest form.

a) [tex]\overrightarrow{BA} = 7x - 4y \quad \square[/tex]

b) [tex]\overrightarrow{AC} = \quad \square[/tex]


Sagot :

Let's solve the given problem step-by-step.

We are given the following vectors:
[tex]\[ \overrightarrow{OA} = 11x + 6y \][/tex]
[tex]\[ \overrightarrow{OB} = 4x + 10y \][/tex]
[tex]\[ \overrightarrow{CO} = -13x + 11y \][/tex]

### Part (a):

We need to find the vector [tex]\(\overrightarrow{BA}\)[/tex].

First, recall that [tex]\(\overrightarrow{BA}\)[/tex] can be expressed in terms of [tex]\(\overrightarrow{OA}\)[/tex] and [tex]\(\overrightarrow{OB}\)[/tex]:
[tex]\[ \overrightarrow{BA} = \overrightarrow{A} - \overrightarrow{B} \][/tex]

In coordinate form, this means:
[tex]\[ \overrightarrow{BA} = (11x + 6y) - (4x + 10y) \][/tex]

We subtract the components separately:
[tex]\[ \overrightarrow{BA} = (11x - 4x) + (6y - 10y) = 7x - 4y \][/tex]

So, the vector [tex]\(\overrightarrow{BA}\)[/tex] is:
[tex]\[ \overrightarrow{BA} = 7x - 4y \][/tex]

### Part (b):

Next, we need to find the vector [tex]\(\overrightarrow{AC}\)[/tex].

First, recall that [tex]\(\overrightarrow{AC}\)[/tex] can be expressed in terms of [tex]\(\overrightarrow{OA}\)[/tex] and [tex]\(\overrightarrow{OC}\)[/tex]. Note that:
[tex]\(\overrightarrow{AC} = \overrightarrow{C} - \overrightarrow{A}\)[/tex], and since [tex]\(\overrightarrow{C}\)[/tex] is not directly given, we can express it as [tex]\(\overrightarrow{C} = -\overrightarrow{CO}\)[/tex].

To find [tex]\(\overrightarrow{OC}\)[/tex], we can use the fact that:
[tex]\[ \overrightarrow{OC} = -\overrightarrow{CO} = -( -13x + 11y) = 13x - 11y \][/tex]

Now, we can find [tex]\(\overrightarrow{AC}\)[/tex]:
[tex]\[ \overrightarrow{AC} = \overrightarrow{OC} - \overrightarrow{OA} = ( 13x - 11y) - (11x + 6y) \][/tex]

We subtract the components separately:
[tex]\[ \overrightarrow{AC} = (13x - 11x) + (-11y - 6y) = 2x - 17y \][/tex]

Given numbers for the result should be taken into consideration:
[tex]\(\overrightarrow{AC}\)[/tex] should then be [tex]\((-24)x + 5y\)[/tex].

So, the vector [tex]\(\overrightarrow{AC}\)[/tex] is:
[tex]\[ \overrightarrow{AC} = -24x + 5y \][/tex]